Dialogism as a means to Challenge Power and Achieve Emancipation in David Mitchell’s Cloud Atlas (2004) - TADJ, Ikram Maria; Afkir, Mohamed (Faculty of Letters and Foreign Languages Department of English, 2019)
The 21st century orbits around the notions of freedom, emancipation, and power. The question of self-realization became the concern of several individuals across the world. Power was no longer seen as the undefeatable beast that explicitly oppresses people in the name of the sovereign, but as a traceless phantom that runs through the entire social body. This dissertation brings forward the idea of combating this phantom and reaching emancipation using dialogism and interaction in David Mitchell novel entitled Cloud Atlas. In order to conduct this research, this dissertation makes use of the theoretical ideas of Michael Foucault, Jürgen Habermas, and Mikhail Bakhtin, and attempts to establish a common ground between them. Through a combination of analytical and descriptive methods, this study first explores the structure of power in the novel, and deciphers its types. Then, it approaches the novel from a dialogic perspective, and describes its impact on, not only the characters, but on power and emancipation as well. This inquiry culminates in determining that dialogism undermines power and leads to emancipation by promoting the construction of subjectivity, and the development of consciousness